Multimodal approach to address the multifaceted nature of Chronic Musculoskeletal Disorders: Bridging the gap between research and clinical practice - Marwa Asim; Muhammad Ehab Azim; Furqan Ahmed Siddiqi; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
Musculoskeletal (MSK) disorders encompass various conditions impacting bones, muscles, tendons, ligaments, and nerves. An estimated 1.71 billion individuals globally have MSK disorders, causing disability and reduced quality of life. Literature contradicts the notion that musculoskeletal pain and disability solely arise from physical impairments; psychological, behavioural, and social factors contribute significantly. These facets influence pain perception and chronic impairment development. Common interventions—medication, exercise, manual and hydrotherapy, electro-thermal modalities, behavioural and alternative therapies—address pain individually, yet lack the comprehensive response required. In contrast, a multimodal approach combines diverse therapies tailored to individual needs. It ensures lasting symptom relief, prevents recurrence, and improves function. Although proven effective, clinical implementation of this approach remains limited. This mini-review discusses the reasons behind this gap, underscores multimodal approach importance, and enlightens rehabilitation professionals on its potential for managing chronic musculoskeletal issues. MeSH Keywords: Humans, Musculosketal Pain, Quality of Life, Social Factors, Hydrotherapy, Complementary Therapies.